IDENTIFIKASI PLASMODIUM MALARIA PADA SEDIAAN TETES TEBAL DI DESA DODAGA - Rony Puasa; Febrianti Jakaria; Irma Irma; B. Hi. Lewa (Poltekkes Kemenkes Pakassar, 2022)
ABSTRACTBackground: Malaria cases that often reoccur in East Halmahera Regency are Dodaga Village, this can be caused by one of them being improper blood sampling in the sense of insufficient volume so that a small amount of Plasmodium malaria is not detected in the sample taken. To avoid identification errors which resulted in repeated cases in Dodaga Village. Purpose ; Identify and count the number of Plasmodium malaria in thick blood preparations using a volume of 10 l and represent the number of positive blood preparations. Methods: This research is a laboratory experimental study with the aim of seeing the accuracy of the volume of blood samples in detecting the presence of Plasmodium malaria. Results ; From the identification of 100 blood samples, with a volume of 10 l, no Plasmodium malaria was found. Conclusion No Plasmodium malaria was found in the respondent's blood supply, which amounted to 100, so it was not possible to calculate the amount of Plasmodium malaria in the respondent's blood supply. Keywords: identification of Dodaga malaria ABSTRAK Latar Belakang : Kasus malaria yang sering kembali terjadi di Kabupaten Halmahera Timur adalah Desa Dodaga ini dapat disebabkan salah satunya adalah pengambilan sampel darah yang tidak tepat dalam arti volume yang kurang sehingga Plasmodium malaria dalam jumlah sedikit tidak terdeteksi dalam sampel yang diambil. Untuk menghindari kesalahan hasil identifikasi yang mengakibatkan masih adanya kasus berulang di Desa Dodaga. Tujuan ; Mengidentifikasi dan menghitung jumlah Plasmodium malaria pada sediaan darah tebal menggunakan volume 10 µl serta mempresentasikan jumlah sediaan darah yang positif. Metode : penelitian ini adalah penelitian eksperimen laboratorium dengan tujuan untuk melihat keakuratan volume sampel darah dalam mendeteksi keberadaan Plasmodium malaria. Hasil ; Dari hasil identifikasi terhadap 100 sampel darah, dengan volume 10 µl tidak ditemuka Plasmodium malaria. Kesimpulan Tidak ditemukan Plasmodium malaria pada sediaan darah responden yang berjumlah 100, sehingga tidak dapat menghitung Jumlah Plasmodium malaria pada sediaan darah respondenKata Kunci : identifikasi malaria Dodaga